Transexualidade e o direito de (não) mudar: políticas públicas e autodeterminação dos/das transexuais em João Pessoa-PB - Silva Júnior, Sebastião Angelim da (2020)
The Federal Constitution of 1988, by favoring the dignity of the human person, guaranteed all individuals the protection of their identities and personalities’ development. Under this approach, each and every citizen, being understood as the main reason for the State's existence, must have their individualities protected. However, transsexual individuals do not enjoy the full citizenship that was granted to them by the constitution due to the fact that their human rights are violated on a daily basis, mainly the right of self-determination to be recognized socially and legally in the same way as they perceive themselves. In Brazil, there is still no federal law regulating the specific civil issues related to transsexual people and the legal and social consequences of that problem. That being said, the present research sought to analyze the socio-legal aspects that involves transsexuality, highlighting the need to deconstruct the pathological ideal of the matter, as well as trying to expose the need for civil and legislative recognition of the topic, especially the right of selfdetermination. For that, the studies of Foucault (1985) were used to address human sexuality, Butler (2003) to discuss the concept of gender, Swain (2001), Bento (2008; 2017) and Louro (2004) to understand the queer theory and transsexuality, among other authors. In order to illustrate the local reality of the research, an overview of public policies for the protection and promotion of diversity developed by the county of João Pessoa-PB was made. The study had a qualitative approach, supported by bibliographical and documentary research, proceeded through direct observation. It was concluded that the heteronormative-scientific discourse that deals with transsexuality as a pathology is no longer supported, and it must be understood from the perspective of the individual's gender identity, and it is of fundamental importance that Brazil creates a federal law that protects the rights of citizenship and personality of transsexual people. Furthermore, João Pessoa's local diagnosis revealed that the county has an effective and praiseworthy network of public policies aimed at the transsexual population and LGBTQIA + as a whole, being a reference to all parts of Brazil.